Optical properties of Fe2+ Ion doped ZnS nanoparticles synthesized using co-precipitation method - Rahizana Mohd Ibrahim; Masturah Markom; Kamal Firdausi Abd Razak (Fakulti Kejuruteraan ,UKM,Bangi., 2015)
Nanoparticles of Zn1-xFexS (x = 0.0, 0.1, 0.2 and 0.3) were prepared by chemical co-precipitation method from homogenous solution of zinc and ferum salt at room temperature with controlled parameter. These nanoparticles were sterically stabilized using Sodium Hexamethaphospate (SHMP). Here, a study of the effect of Fe doping on structure and optical properties of nanoparticles was undertaken. Structure, elemental analysis and optical properties have been investigated by X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM), Fourier-Transform-Infrared spectroscopy (FT-IR), X-Ray Fluorescence (XRF), UV-Visible Spectroscopy and photoluminescence (PL) spectrophotometer. FT-IR and XRF results confi rmed the incorporation of ion dopants into ZnS crystal structure, and XRD results showed that Zn1-xFexS (x = 0.00 and 0.10) nanoparticles crystallized in a zinc blende structure without any impurity. The particle size of all of samples ranged from 2 nm to 3 nm, as calculated by the Debye-Scherrer formula. The optical absorption spectra indicate a blue shift of the absorption edge with increasing Fe-content. The luminescence of nanoparticles excite at about 370 nm with an emission peak at around at 452 nm, 490 nm and 550 nm.